Students Learning Interest in WhatsApp-Based Online Learning During Covid-19 Pandemic in Class VIII MTs Al-Hidayah Tosiba - Nurhidayah, Nurhidayah; Tendrita, Miswandi; Saparuddin, Saparuddin (Journal of Biological Science and Education, 2023)
Online learning was carried out during the Covid 19 pandemic. During online learning, many students were less active. This research aims to find out how interested students are in WhatsApp-based online learning in science subjects. The type of research used is quantitative descriptive research. The number of samples used in this research was 42 class VIII students at MTs Al-Hidayah Tosiba taken using a purposive sampling technique. The instrument used in this research was a questionnaire with a total of 20 statement items. Student interest in learning can be seen from 4 indicators, namely: feelings of happiness, student interest, student attention and student involvement. The results of this research show that the indicator of feelings of happiness is 54.76% in the "moderate" category. The interest indicator is 45.24% in the "very low" category. The attention indicator is 35.71% in the "high" category. The engagement indicator is 45.24% in the "high" category. Overall, the average of the questionnaire data obtained was 53.85 with the highest percentage of 33.33% being in the "medium" category. Based on the results of this analysis, it can be concluded that students' interest in learning in WhatsApp-based online learning is moderate.Â Keywords: Interest in Learning, Science, Online LearningÂ